Dynamic characteristics of RC structures in short and long duration real fires. (June 2022) - Noman, Muhammad; Yaqub, Muhammad; Fahad, Muhammad; Butt, Faheem; Khalid, Basit
Abstract: The change in the dynamic behaviour of reinforced concrete (RC) structures after the fire events is still an unsolved issue for research communities and regulatory authorities. To fill the gap, this paper presents the experimental results of the shift in dynamic characteristics of a single scaled-down two-storey RC structure after exposure to short and long-duration real fires. The structure having normal strength concrete was constructed and well-instrumented with temperature sensors to obtain a large database of temperature profiles in the compartment and various element sections. Short Duration Fire Test (SDFT) of 20 min with a maximum temperature of 852 °C and Long Duration Fire Test (LDFT) of 100 min with a maximum temperature of 813 °C were created using wooden logs to represent a realistic office fire. The structure was further tested for dynamic characteristics such as natural frequencies and mode shapes by gently hitting it with a mass source that generated an impulse leading to free vibration in the structure. The natural frequency reduction of 14.71% and 49.5% were observed after the structure was exposed to short and long duration fires respectively. The mode shapes after the fires also showed variation indicating damages in the structure due to fires. The study will be useful in understanding the dynamic behaviour of structures in short and long-duration real fires as well as it will serve as a database for numerical modelling of RC structures.